The improvement of voltage sags pattern approach to locate a fault in distribution network - Mokhlis, Hazlie; Bakar, A.H.A.; Talib, D.N.A.; Mohamad, H. (Praise Worthy Prize, 2010)
This paper describes an improvement of a faulted section identification method. The improvement has made the method not only able to identify a faulted section, but at the same time calculate fault distance from one-end of the faulted section. By having this new feature, the locating fault time can be further reduced. The method has been tested on an actual underground rural distribution network feeder with all type of fault. The results show that most faults can be located by the first attempt and with high accuracy of fault distance. Only few faulted sections found by the second attempt. Since the proposed method is using only voltage sag data, monitored at the primary substation, the method is considers economical to be implemented for a rural distribution network.